Does the use of hormonal contraception increase the risk of breast cancer in women of reproductive age (15-49 years)? : A Systematic Review - Rizky Febriansyah; Bangar Parlinggoman Tua; Mutia Juliana; Aditya Rifandi Zaenudin (The International Journal of Medical Science and Health Research, 2026)
Introduction: Hormonal contraception is widely used by women of reproductive age worldwide, yet concerns persist regarding its potential association with breast cancer risk. Despite numerous studies, heterogeneity in findings across populations and contraceptive types has created uncertainty for clinicians and users. This systematic review aims to evaluate the relationship between hormonal contraceptive use and breast cancer risk in women aged 15-49 years, examining variations by contraceptive type, duration, formulation, and population characteristics. Methods: A systematic review was conducted of 80 studies examining hormonal contraception and breast cancer risk in reproductive-age women. Included studies comprised cohort studies, etc. Data were extracted on study design, population characteristics, contraceptive type and duration, breast cancer outcomes, risk measures, and effect modifiers. Studies were assessed for methodological quality and risk of bias. Results: Large prospective cohort studies demonstrated consistently increased breast cancer risk with current or recent hormonal contraceptive use (relative risks 1.20-1.33) (1,3,5). Risk varied by formulation: triphasic levonorgestrel (RR=3.05) (3), high-dose estrogen (OR=2.7) (8), and ethynodiol diacetate (OR=2.6) (8) showed strongest associations, while low-dose formulations showed minimal risk (OR=1.0) (7). Duration-response relationships were evident, with risk increasing from 1.09 for <1 year to 1.38 for >10 years use (1). Progestogen-only methods showed comparable risks: oral (OR=1.26), injectable (OR=1.25), and levonorgestrel-IUD (OR=1.32) (10). Risk dissipated within 5-15 years after cessation (12,13). Absolute excess risks were age-dependent: 8 per 100,000 women-years for ages 16-20 versus 265 per 100,000 for ages 35-39 (2). Southeast Asian studies reported higher odds ratios (2.66-9.06) (17-19), likely reflecting methodological differences rather than true population variation. Discussion: The evidence supports a modest, transient increase in breast cancer risk with hormonal contraceptive use that varies substantially by formulation, duration, and age. Contemporary low-dose formulations confer minimal risk. The rapid risk dissipation after cessation suggests a promotional rather than initiating mechanism. Absolute risks remain small, particularly for women under 35 years, and must be balanced against the established benefits of pregnancy prevention and non-contraceptive health benefits. Conclusion: Hormonal contraception is associated with a small increased risk of breast cancer during use that declines after cessation. Formulation-specific differences exist, with contemporary low-dose preparations demonstrating the most favorable risk profile. Clinicians should provide individualized counseling considering age, contraceptive needs, and risk factors, emphasizing that absolute risks are minimal for most reproductive-age women.